The politics of teaching time in disciplinary and control societies. Issue 1 (2nd January 2017) - Thompson, Greg; Cook, Ian
Abstract: This article argues that education reform agendas which use policy levers, standardised testing and new regulatory authorities to steer teachers' work at a distance are creating a new temporal politics. Evidence from interviews with teachers and principals in Australian schools suggests that these reforms are impacting on individual experiences of the rhythms of their day-to-day work. First, there is a disquieting perception of an acceleration of their working life. Second, and related, many teachers and principals spoke of feeling 'out of time', or out of rhythm, with the new expectations of their work. Using Deleuze's control societies, we posit that this arrhythmia exemplifies the experience of the classroom being 'opened up' for the purposes of comparison. This breakdown of the enclosed classroom is affected through the datafication of teaching.